1991
DOI: 10.1111/j.1464-410x.1991.tb15428.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Rupture of the Corpus Cavernosum

Abstract: Twelve patients with fracture of the penis have been treated in this department during the last 18 years. Their mean age was 41.5 years (range 25-55) and two-thirds of the injuries resulted from coitus. Eleven patients underwent immediate exploration and repair of the tunica albuginea and only 1 still has sexual dysfunction. One patient was treated conservatively and remains impotent. Immediate surgical treatment is recommended, since it avoids the formation of penile plaque, penile fibrosis and angulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 8 publications
0
14
0
2
Order By: Relevance
“…However, despite supportive measures such as pain relief, pressure dressings, pharmacological suppression of erection, anti-inflammatory agents, empirical antibiotics and catheterization, a 10-30% incidence of residual penile curvature has been associated with nonoperative management [32,54]. Other reported complications include penile abscess, missed urethral injury, persistent haematoma, fibrosis and angulation.…”
Section: Managementmentioning
confidence: 99%
“…However, despite supportive measures such as pain relief, pressure dressings, pharmacological suppression of erection, anti-inflammatory agents, empirical antibiotics and catheterization, a 10-30% incidence of residual penile curvature has been associated with nonoperative management [32,54]. Other reported complications include penile abscess, missed urethral injury, persistent haematoma, fibrosis and angulation.…”
Section: Managementmentioning
confidence: 99%
“…In the current series, one urethral injury was documented (8%). El-Sherif et al 6 attributed the similarly low incidence in their series to the high incidence of non-coital fractures, whereas Tan et al 25 reported a similarly low incidence despite a high percentage of coital fractures in their series. It is therefore not clear what predisposes to urethral injuries in association with fractured penis.…”
Section: Discussionmentioning
confidence: 73%
“…1,6,[23][24][25] The mean age in this series, 36 years, falls within this range. In seven of our 12 patients (57%), the fracture incidents were related to sexual intercourse, which is similar to the 58% reported by Nicolaison et al 24 from the West, but varies greatly with the 9.5% reported by El-Sherif et al 6 from a neighboring Gulf state.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations